STRESS RELATED HAIRLOSS IN MEDICAL STUDENTS - Abeer Fatima; Muhammad Danial Ali; Mahpara Safdar et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: Stress is a psychological and physical disorder involving the feeling of [1] [2]incompetence, anger, uselessness and guilt. Hair has potent importance in feminine personality. Stress induces adaptive immunity leading to cytokines imbalance increasing the apoptosis of epithelial cell of hair. OBJECTIVE: The objective of our study was to evaluate hair loss among medical students and its relationship to stress. MATERIAL AND METHODS: STUDY DESIGN: Cross sectional study STUDY SETTING AND DURATION: 3 months, April 2017-June 2017 INCLUSION CRITERIA: All medical students of either gender of Allama Iqbal Medical College. DATA COLLECTION AND ANALYSIS: The participants of our study were MBBS students of AIMC from all the ﬁve years. To form a representative sample of 300 our team approached 60 students from each class. The participants responded to the questionnaire based on two sections. Section I showed the level of hair loss and its relation to various factors. Section II of the questionnaire was based on perceived stress scale (0 = Never to 4 very often). Out of total score of 24, subjects with PSS scores ranging from 0-13 were considered low stress, score ranging from 14-26 were considered moderate stress and scores ranging from 27-40 were considered high perceived stress. Using SPSS version 23.0, we calculated the frequencies of type of hair loss, pattern of hair loss, duration of hair loss and stress. Then we compared the frequencies of hair loss and stress, applied chi square test. RESULTS: Out of 300 students 257 students (85.67%) experienced hair loss while 43 students (14.33%) did not experience hair loss .out of these 257 students 75 (25%) experienced mild hair loss,146(48.7%) experienced moderate hair loss whereas 36(12%)experienced extreme hair loss. Cross tabulating the stress grade with hair loss showed that majority of hair fall victims had moderate to severe stress (P < 0.05). CONCLUSIONS: The conclusion of my study was that hair fall is common among students of Allama Iqbal Medical College and there is signiﬁcant association between stress and hair loss.